2016
DOI: 10.4172/2169-0138.1000126
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antigenic Determinants, Solvent Accessibility and MHC Binders of Antigen NADH Dehydrogenase Subunit 5 from a Little Dragon from Medina (Dracunculusmedinensis)

Abstract: Dracunculiasis caused by the pathogen Dracunculus medinensis (a little dragon from Medina). The Cyclops is the intermediate host that ingests the larvae of parasite (D. medinensis), that later on ingested by the human from the contaminated stagnant unfiltered water from the water source. After an incubation period of a year these mature female worm comes towards the skin and start formation of a small round bulge on the skin by secreting an irritating chemical which causes severe pain. In this study we will su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…We found that the LF of other species could also be recognized by this anti-bLF monoclonal antibody, because we used conserved regions, and seven amino acids (XXQXKFGKXXXXXFQ), as antigens. Glutamine Q (3,15), lysine K (5, 8), Phenylalanine F (6,14), Glycine G (7) might represent the potential epitope recognized by our lactoferrin monoclonal antibody (Figure 5). However, further studies are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the LF of other species could also be recognized by this anti-bLF monoclonal antibody, because we used conserved regions, and seven amino acids (XXQXKFGKXXXXXFQ), as antigens. Glutamine Q (3,15), lysine K (5, 8), Phenylalanine F (6,14), Glycine G (7) might represent the potential epitope recognized by our lactoferrin monoclonal antibody (Figure 5). However, further studies are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid sequence of Bos taurus lactoferrin containing 708 amino acids (NP_851341.1) was obtained from the National Center for Biotechnology Information (NCBI). bLF antigen regions were carefully predicted based on antigenicity and hydrophobicity of the whole amino acid sequence using the online software ProtScale at https://web.expasy.org/protscale/ (accessed on 18 May 2017) (ExPASy, Switzerland) [13][14][15]. A 16-mer peptide of KAQEKFGKNKSRSFQ from bovine lactoferrin corresponding to amino acids 292-306 was selected as the immunogen.…”
Section: Peptide Conjugationmentioning
confidence: 99%